Baseline prevalence and predictors of liver fibrosis among HIV‐positive individuals: a substudy of the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Matthews, GV; Neuhaus, J; Bhagani, S; Mehta, SH; Vlahakis, E; Doroana, M; Naggie, S; Arenas‐Pinto, A; Peters, L; Rockstroh, JK; ,
Abstract : Objectives: Liver disease is increasingly recognized in HIV‐positive individuals, even among those without viral hepatitis, partly as a result of the recent availability of noninvasive methods of liver fibrosis assessment. The objective of this substudy is to compare the effects of early versus deferred antiretroviral therapy (ART) on liver fibrosis progression. Methods: Sites in the Strategic Timing of AntiRetroviral Treatment (START) study with access to FibroScan® were invited to participate in the Liver Fibrosis Progression Substudy. All substudy participants underwent FibroScan® at baseline, and two noninvasive serum algorithms, APRI and FIB‐4, were calculated. Demographic and liver‐related information was collected for all START participants at baseline. Results: A total of 230 participants were enrolled in the substudy (11.5% with hepatitis B or C virus coinfection), of whom 221 had a valid transient elastography (TE) result. The median TE score was 4.9 kPa [interquartile range (IQR) 4.3–6.0 kPa]. Seventeen patients (7.8%) [95% confidence interval (CI) 5.1–12.1%] had a TE score of > 7.2 kPa, indicating significant liver fibrosis. Baseline factors associated with higher TE scores in multivariate analysis were higher alanine aminotransferase (ALT) per 10 U/L ( P  = 0.045), higher log10 HIV RNA ( P  < 0.001) and Hispanic/Latino ethnicity ( P  = 0.01). TE correlated weakly with noninvasive markers. Conclusions: At baseline, significant liver fibrosis was observed in approximately 8% of participants, with higher ALT and HIV RNA the only clinical factors associated with increasing TE score. TE will be used annually to monitor fibrosis and evaluate the role of ART in further fibrosis progression.